PLASMA SURFACTANT PROTEIN-A LEVELS IN HEALTHY SUBJECTS AND CHRONIC OBSTRUCTIVE PULMONARY DISEASE PATIENTS - Waseem, Hafiz Muhammad; Khan, Rida Ajmal; Lone, Khalid Parvez (Journal of Ayub Medical College Abbottabad, 2020)
Background: Chronic Obstructive Pulmonary Disease (COPD) is the leading cause of morbidity and mortality across the globe. Currently, there is a dearth of biomarkers which can accurately diagnose and evaluate the prognosis of the disease. Systemic Surfactant Protein- A (SP-A) levels are generally higher in smokers compared to non-smokers as well as elevated in COPD patients as compared to controls. The objective of the study was to estimate and compare plasma surfactant protein-A levels in male and female COPD patients and healthy subjects and to evaluate the role of SP-A as a possible bio-marker for COPD patients. Methods: A Comparative study, conducted at the department of Physiology & Cell Biology, University of Health Sciences, Lahore between August 2013 and April 2015. A total of 84 subjects of both sexes between 30-80 years of age were included in this study. Subjects were taken from local community and were divided into four groups (A- D). COPD was diagnosed on the basis of relevant history and spirometry showing post bronchodilator FEV1/FVC <0.70. Results: Plasma SP-A levels were not different between controls and COPD patients and between male and female COPD patients. However, SP-A levels were directly correlated with cotinine levels (r= 0.503, p=0.001). Female patients were usually more symptomatic than males and developed COPD at an earlier age compared with male patients. Conclusion: Plasma SP-A levels were not significantly different between groups. Plasma cotinine levels (an indication of the tobacco use) were positively correlated with plasma SP-A levels in study subjects. Female patients developed COPD at an early age compared to male counterparts with similar tobacco exposure. Keywords: Chronic Obstructive Lung Disease, Surfactant Protein A, Cotinine, Spirometry, Smoking